Evaluation of larvicidal activity of polar and nonpolar extracts from acetogenins of Annona muricata on Aedes aegypti and Anopheles albimanus larvae (Díptera: Culicidae) - MORALES, CARLOS ANDRÉS; GONZÁLEZ, RANULFO; ARAGÓN, RAÚL (Revista Colombiana de Entomología, 2004)
Many species of higher plants produce secondary metabolites, to which ecological functions and defense against microorganisms and phytophages are attributed. The objective of this work was to understand the susceptibility of Ae. aegypti and An. albimanus larvae to two types of acetogenins extracts obtained from seeds of Annona muricata. The two species of Culicidae studied were highly susceptible to both kinds of extracts under laboratory conditions. The mean lethal concentrations (CL50) for the polar, nonpolar and mix of acetogenins extracts for Ae. aegypti were 74,7 ppm, 236,2 ppm and 20,3 ppm, respectively, while in An. albimanus they were 0,8 ppm, 16,2 ppm and 1,4 ppm. The diagnostic doses are presented with their respective range of variation. The differences in mortality produced by the extracts were not statistically significant. An option for its use could eventually be determined when the residuality of both compounds and the cost-beneflt ratio are evaluated.